Yield measurements at IGISOL with a digital data acquisition system - Khanam, Afrina (2017)
A new digital data acquisition system has been installed at the IGISOL facility at the department of Physics in University of Jyväskylä in November, 2016. The technical details of the hardware and software of this new system are presented in this thesis. Nutaq VHS-ADC digital data acquisition system includes an analogue to digital converter (ADC) crate board, an offset unit box, an acquisition host PC, and a storage drive. This system consists of 8 channels, has the capability of 105 MSPS with 14-bit ADCs on 6U cPCI (PXI compatible). Radioactive sources, beta-gamma matrix, gamma-gamma matrix, beta-delayed gamma, and gamma-delayed gamma spectra of radioactive isotopes produced at IGISOL were studied. Two online experiments were successfully performed with this system. Yield of 20F in the first online commissioning was studied. Yields at A= 76 and A= 81 mass region in the second online commissioning experiment were studied with a 3π∆Eβ scintillator and a coaxial Ge detector, GC-7020 were found consistent with the number of yields calculated with beta counting station at the IGISOL switchyard. Efficiency of 3π∆Eβ scintillator detector, efficiency of the silicon detector, CAN-B(FD-300-17-500-RM) in beta counting station and efficiency calibration for the Ge detector(GC-7020) were determined.